Quantifying the relative importance of stock level, river temperature and discharge on the abundance of juvenile Atlantic salmon (Salmo salar). Issue 6 (14th July 2020) - Glover, Ross S.; Soulsby, Chris; Fryer, Robert J.; Birkel, Christian; Malcolm, Iain A.
Abstract: Fisheries scientists need to understand the relationships between river temperature, discharge and production of juvenile salmonids to inform evidence‐based management and regulation of rivers and to understand the potential effects of climate change. These relationships can be determined by characterising interannual variability in abundance and environmental conditions from long‐term monitoring data and assessing their inter‐relationships. Two major challenges are (1) the requirement to separate the relative effects of stock level and environment which both affect interannual variability in abundance and (2) obtaining long‐term environmental time‐series that do not suffer from temporal biases. This study built on recent advances in hydrological, river‐temperature and juvenile salmonid modelling to investigate the influence of temperature and discharge on interannual variability in Atlantic salmon ( Salmo salar ) fry (age: 0 years) and parr (age: 1 year) production. The study used a unique long‐term dataset (>50 years) with detailed age‐differentiated census data collected for multiple life‐stages. The study shows that most of the interannual variability in recruitment was explained by stock level. Discharge had a comparatively small effect on fry recruitment, but a greater effect than artificial stocking. Discharge had no discernible effect on parr recruitment. Temperature had no effect on recruitment of either life‐stage. This study suggests that salmon are well adapted to current environmental variability in natural upland rivers in Scotland, but reductions in discharge during spawning and emergence could negatively affect fry recruitment with consequences for regulation of river flows. The study highlights the importance of high‐quality census data for accurately determining the effects of environmental variability on recruitment.